Efektivitas Pendampingan Orang Tua Terhadap Tingkat Pemahaman Seksual Remaja - Kalis Stevanus; Hardiyanti Setyorini; Yunianto Yunianto (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
Adolescence is a period of transition from childhood to adulthood. During this period, adolescents experience various developments, and one of them is related to their sexuality. In the development of sexuality, adolescents have a great curiosity related to their reproductive organs. This is where the important role of parental assistance is so that teenagers have the correct information about sex. The purpose of this study was to prove the effectiveness of parental assistance on the formation of adolescent sexual behavior. This research is a type of quantitative research that is descriptive and associative. The results show the fact that there is a very significant influence of the role of parental assistance on the formation of adolescent sex behavior by 71.1%.